Integration testing based on indirect interaction for embedded system - Muhammad Iqbal Hossain; Woo Jin Lee (International Journal of Reconfigurable and Embedded Systems (IJRES), 2019)
Embedded systems comprise several modules that exchange data by interacting among themselves. Exchanging wrong resource data among modules may lead to execution errors or anomalies. Interacting resources produce dependencies between two modules where any change of resources by one module affects the functionality of another module. Several investigations of the embedded system such as aerospace or automobile system show interaction faults between modules are one of the major cause of critical software failures. Therefore, interaction testing is an essential phase to reduce the interaction faults and minimize the risk. The direct and indirect interaction between modules generates interaction faults where indirect interaction is made underneath the interface in which data dependence relationship with resources may cause a different outcome. We investigate errors based on the indirect interaction between modules and introduce a new test criterion for finding errors detectable by existing approaches in unit level but not in integration level. In this paper, we propose a noble approach to generate an interaction model using indirect interaction pattern and design test criteria based on different interaction errors to generate test cases. Finally, we use fault injection and data flow coverage techniques to evaluate the feasibility and effectiveness of our approach